Comparative Analysis Of Performance Appraisal Foreign Banks And Non Foreign Bank Conventional In Indonesia - Bramastyo Kusumo Negoro; Enny Istanti; Achmad Daengs GS (International Journal of Economics and Management Research, 2023)
This study aims to compare the performance of conventional foreign exchange banks and conventional non-foreign exchange banks in Indonesia during 20 20 -20 2 1 using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). This study using ROA, NPL, CAR, LDR, Institutional Ownership, Managerial Ownership, and the Commissioner of the Independent variable Samples were selected in this study with purposive sampling method amounted to 105 foreign banks and 15 non-bank foreign exchange during 20 20 -20 2 1. Analysis that using Independent t-tests on the data were normally distributed and the Mann Whitney-U test on the data is not normally distributed. In the test results stated that there are no differences in the financial performance of foreign exchange banks and non-foreign exchange banks if in view of the ratio of ROA, NPL , CAR, and LDR. And there are differences in the level of performance when viewed in terms of ownership and leadership.